Expanding the UK Secure by Design proposal for a usable consumer-focused IoT security label - MATHEW ESTIENNE (2023)
No person whom has any knowledge of security in the Internet of Things (IoT) would claim the current landscape is desirable, as exceedingly poor security of devices is routinely exhibited in an ecosystem experiencing exponential growth of devices. If these devices follow past trends in Cyber Security, it is not unreasonable to assume that without intervention another decade of exponentially growing costs attributed to Cyber Crime may lay ahead. After the failure of the voluntary approach to IoT Security, works are now being taken to legislate a minimum security standard.Building from existing proposals, this paper outlines real improvements that could be made to current ongoing works, with the intention of providing incentive for manufacturers to improve device security in the IoT sector and reduce the timeline for routine deployment of secured devices.Incorporating strategies developed in other industries, as well as security requirements from across international borders, a point-of-sale user focused label is proposed, which can be easily interpreted by non-technical users. Intending to provoke curiosity and fully reassure the end-user, a two-layer system is chosen which allows the conveyance of more detailed information than could fit on a physical label.